Analysis of Policy Frameworks for Integrating ICT in Ghanaian Education: Implications for Teacher Education and Professional Development: A Systematic Review (American Journal of Education and Technology, 2023)
This study examines the policy frameworks surrounding integration of Information and Communication Technology (ICT) into the Ghanaian education system. This study investigated the implications of these policy frameworks on teacher education and professional development. By exploring existing policies, strategies, and initiatives, this study aims to provide insights into the challenges and opportunities associated with ICT integration in Ghanaian classrooms. This study adopted a descriptive and qualitative research design, employing document analysis in teacher education and training.¬ The collected policy documents were analysed using a thematic approach, enabling the identification of recurring patterns and themes related to ICT integration policies and their impact on teacher education. The findings revealed that Ghana has made commendable efforts to formulate policy frameworks to facilitate ICT integration in education. However, several challenges persist, including limited access to ICT resources, inadequate teacher-training programs, and uneven implementation across schools and regions. The research article concludes with recommendations for policymakers, educators, and other stakeholders in the Ghanaian education system. These recommendations include establishing a robust ICT infrastructure, providing equitable access to technology, designing, and implementing effective teacher training programs, and developing a supportive policy environment that encourages continuous professional development.